2017
DOI: 10.1371/journal.pone.0173398
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease and increased risk of 1-year all-cause and cardiac hospital readmissions in elderly patients admitted for acute heart failure

Abstract: Nonalcoholic fatty liver disease (NAFLD) is an emerging risk factor for heart failure (HF). Although some progress has been made in improving survival among patients admitted for HF, the rates of hospital readmissions and the related costs continue to rise dramatically. We sought to examine whether NAFLD and its severity (diagnosed at hospital admission) was independently associated with a higher risk of 1-year all-cause and cardiac re-hospitalization in patients admitted for acute HF. We studied 212 elderly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 36 publications
0
22
0
1
Order By: Relevance
“…Prior studies have noted an association between NAFLD and indices of impaired relaxation and increased left-sided chamber pressures on echocardiography 14,17,18,24 . This finding is important given that prior data that has shown that liver disease stage is strongly linked with outcomes among patients with heart failure 9,25 . More advanced liver fibrosis has been associated with volume overload, diastolic dysfunction, impaired exercise capacity, and higher mortality in patients with HFpEF 5,8,9 .…”
Section: Discussionmentioning
confidence: 75%
“…Prior studies have noted an association between NAFLD and indices of impaired relaxation and increased left-sided chamber pressures on echocardiography 14,17,18,24 . This finding is important given that prior data that has shown that liver disease stage is strongly linked with outcomes among patients with heart failure 9,25 . More advanced liver fibrosis has been associated with volume overload, diastolic dysfunction, impaired exercise capacity, and higher mortality in patients with HFpEF 5,8,9 .…”
Section: Discussionmentioning
confidence: 75%
“…Those with severe liver disease might experience coagulation dysfunction, anemia, and increased cardiac effort [ 35 ]. Recently, nonalcoholic fatty liver disease has been identified as an emerging risk factor for acute heart failure [ 36 ]. This might partially explain our finding about liver disease and PCHF.…”
Section: Discussionmentioning
confidence: 99%
“…Lebererkrankungen sind zudem vermutlich über Entzündungsmediatoren wie Interleukin-6, pro-inflammatorische Zytokine und via Insulinresistenz mit einem erhöhten Anteil kardiovaskulärer Erkrankungen verbunden [17]. Die italienische Arbeitsgruppe um Giovanni Targher beobachtete bei älteren Patienten, die aufgrund kardiovaskulärer Ereignisse stationär behandelt werden mussten, dass mehr als jeder zweite eine NAFDL aufwies und gleichzeitig ein deutlich erhöhtes Risiko, innerhalb eines Jahres aufgrund kardiovaskulärer Ereignisse erneut in ein Krankenhaus aufgenommen werden zu müssen [25].…”
Section: Lebererkrankungen Sind Mit Erhöhter Morbidität Und Mortalitäunclassified